2021
DOI: 10.4324/9781003158462
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian and Ghanaian Women Working in the Brussels Red-Light District

Abstract: A groundbreaking book on the lives of immigrant sex workers in Europe. Focused on West African women who work in window-pros titution rooms in Brussels and based on carefully conducted field observations and interviews, the book offers unique findings, insights, and policy recommendations regarding the women's lives, work, and struggles in a disadvantaged, crime-ridden part of the city that does not receive the police protection it deserves. A major contribution to our understanding of the lives of marginalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, for many, the experiences of violence do not end after arrival in Italy, as they are forced into prostitution and beaten by clients, pretend clients, and traffickers alike. A recent study [48] among Nigerian women working in prostitution in the Brussels Red-Light District (many of whom were undocumented and arrived in Europe via the central Mediterranean route as well) also found that one of the women's biggest concerns was safety. This was because of experienced violence at the hands of clients and pretend clients who raped them, attempted to do so, robbed, or attacked them, and violence perpetuated by locals who attacked them because they did not want them there.…”
Section: Discussionmentioning
confidence: 99%
“…However, for many, the experiences of violence do not end after arrival in Italy, as they are forced into prostitution and beaten by clients, pretend clients, and traffickers alike. A recent study [48] among Nigerian women working in prostitution in the Brussels Red-Light District (many of whom were undocumented and arrived in Europe via the central Mediterranean route as well) also found that one of the women's biggest concerns was safety. This was because of experienced violence at the hands of clients and pretend clients who raped them, attempted to do so, robbed, or attacked them, and violence perpetuated by locals who attacked them because they did not want them there.…”
Section: Discussionmentioning
confidence: 99%
“…The participants referred to her as “big sis,” “sister,” or “aunty,” all terms of endearment and respect used when referring to someone who is older than you in the Nigerian culture. The researcher therefore had to constantly find the balance between her role as a researcher working at a Belgian institution and as “aunty researcher” as perceived by the participants, highlighting the balance that researchers often seek to find in situations like these (Adeyinka et al, 2021; Samyn et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…These oaths are taken by the women before embarking on the journey before deities such as Ayelala, a deified deity who is invoked to ratify an oath between two parties and believed to cause diseases or calamity to befall whoever breaks the oath (Ojo, 2014;Oviasuyi et al, 2011). Therefore, before the commencement of the journey to a European country, the women are taken to the shrine of a juju doctor/ritualist who performs a juju rite/ oath-taking ritual on them (Adeyinka et al, 2021;van der Watt & Kruger, 2017). The ritualist's job is to ensure that the women vow (1) to never reveal the identity of the person taking them to Europe; (2) that they will repay the cost of the trip as demanded from them; and…”
Section: Jujumentioning
confidence: 99%